Integrating Leadership Training Model in Construction Project Management Programs - AGPARB, Andi Nurkia; NUR, Hasanah; IDHAM, Andi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This research aims to develop a Leadership Training Model within the sphere of Construction Project Management, intended to enhance leadership skills crucial for the successful execution of projects with respect to cost, quality, timing, and administrative order. Employing the Research and Development methodology, this study adopts the ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through a literature review, field surveys, interviews, and questionnaires. The research phases included needs analysis, model design, prototype development, model implementation, and evaluation. The validity and reliability of the instruments were tested using Validity Coefficient (Va) and Percent Agreement (PA). The findings indicate that (1) the Training Needs Analysis revealed a strong influence of leadership styles on cost, quality, and time accuracy in construction project success; (2) the designed training model considered various aspects including materials, guidelines, and training tools, establishing a strong foundation for leadership in construction project management; (3) the model was validated by experts, confirming its validity and innovative applicability for construction stakeholders; (4) the developed training model proved to be practically valuable, as demonstrated by the facilitators’ ability to utilize the training guides and modules effectively; (5) the model was effective in enhancing leadership skills, evidenced by the pre-test and post-test results; (6) the training participants responded positively to the leadership training model for construction project management, regarding it as an innovative and continuous effort in transforming construction projects.